Atkák agrár-ökoszisztémákban: a Macrochelidae (Mesostigmata) család szerepe a növényvédelemben - Kontschán, Jenő; Ács, Anita; Bozsik, Gábor; Kerezsi, Viktor; Szederjesi, Tímea; Szőcs, Gábor (GEORGIKON FOR AGRICULTURE, 2017)
The new results about the mite family Macrochelidae in agricultural ecosystems are summarized. Most important information about the morphology, ecology and their role in the plant protection are given with the notes to newly collected species in agricultural and horticultural soils, composts, beehives and in association with pests. The frequent macrochelid mite species [Macrocheles glaber (Müller, 1860)] was often collected in the agro-ecosystems, like soils of agricultural areas, beehives, composts and on the body on pest insect. Due to their behavior and wide distribution this species may have important role in the regulation of the population of the pest species.